Correction to: Immunomodulatory effects of a new whole ingredients extract from Astragalus: a combined evaluation on chemistry and pharmacology - Zhi Xin Li; Guan Ding Zhao; Wei Xiong; Ke Gang Linghu; Qiu Shuo Ma; Wai San Cheang; Hua Yu; Yitao Wang (BMC, 2021)
An amendment to this paper has been published and can be accessed via the original article.